Advantages of a new improved oblique Retractor in oblique lateral lumbar interbody fusion: a retrospective study - Jun Mo; Siping Zhang; Zhanjun Ma; Jianjiang Li; Yifei Huang (Journal of Orthopaedic Surgery and Research)
Abstract A clear surgical field of view is one of the key factors for a smooth operation. Whether a new modified oblique retractor can improve the field of view during oblique lumbar interbody fusion (OLIF) surgery and thus shorten the surgical time and reduce blood loss needs to be evaluated. A total of 64 patients who were diagnosed with L4‒5 segment lumbar spondylolisthesis, lumbar spinal stenosis, or lumbar disc herniation and who underwent OLIF surgery in our hospital between January 2023 and December 2023 were retrospectively enrolled. They were divided into two groups on the basis of whether the new modified oblique retractor was used: 32 cases with the new modified oblique retractor and 32 cases with a traditional right-angle retractor. Clinical efficacy was compared between the two groups using the visual analogue scale (VAS) for lower limb pain and the Oswestry Disability Index (ODI). The safety in the perioperative period was compared between the two groups using indicators such as surgical time, intraoperative blood loss, the vertebral canal area, and complications. No statistically significant differences were found in the baseline data (age, sex, or BMI) between the two groups (P > 0.05). There were no significant differences in the postoperative VAS score, postoperative ODI, postoperative vertebral canal area, or incidence of complications between the two groups (P > 0.05). There was a statistically significant difference in surgical time and intraoperative blood loss (P < 0.05) between the two groups. Compared with traditional right-angle retractors, the newly improved oblique retractor is more suitable for the surgeon’s field of view, thereby shortening the surgical time to some extent and reducing blood loss. By reducing traction on the psoas major muscle, the possibility of psoas muscle weakness can be decreased. Although there are differences in overall efficacy between the two groups of patients, these differences are small. The newly improved oblique retractor is better in terms of the appropriate surgical field of view angle and provides easier assistant cooperation, thus it is worth promoting and applying in clinical practice.